PARENT IDENTIFICATION IN A MULTI LOCATION TRIAL SEED ORCHARD OF ACACIA MANGIUM USING MICROSATELLITE MARKERS - Nurtjahjaningsih, I. L. G. (Indonesian Journal of Forestry Research, 2016)
Variation of parent gametes' contribution might affect the growth patterns among offspring produced from seed orchards. This paper studies the mating system statuses and to identify parent trees that produce good growth performance of offspring in seedling seed orchard of A. mangium. The study was conducted in two seed orchards, i.e. a first generation seedling seed orchard (F1 SSO) of A. mangium, used as the parent population hereafter and a multi location trial (MLT) as an offspring population. Based on 10 microsatellite markers, mating system in the F1 SSO was under panmictic equilibrium condition. The good growth trees in the MLT originated from various parent genes contribution in the F1 SSO. Several behaviors were observed: a). the best trees in MLT dominantly originated from singlepair trees, between maternal and paternal trees, in F1 SSO; b). a maternal tree was pollinated by two paternal trees; c). a paternal tree pollinated several maternal trees. Flowering synchronization and genetic compatibility among trees might be responsible for these mating system patterns. In order to maximize seeds production, studies on male and female flowers characteristic should be employed to assess flowering synchronization among individual trees in the seed orchard.